Synthesis, Biological Evaluation, and Molecular Docking Studies of Novel Coumarin–Triazole–Isatin Hybrids as Selective Butyrylcholinesterase Inhibitors - Dimovski, Aleksandar; Dobričić, Vladimir; Simić, Milena R.; Jurhar Pavlova, Maja; Mihajloska, Evgenija; Sterjev, Zoran; Poceva Panovska, Ana (MDPI AG, 2025)
A series of 21 novel coumarin–triazole–isatin hybrids was synthesized and evaluated for their potential as multitarget agents in Alzheimer’s disease (AD). The compounds featured variations in alkyl linker length that connects coumarin and triazole and substitution at the 5-position of the isatin ring. Several derivatives showed potent butyrylcholinesterase (BChE) inhibition with selectivity over acetylcholinesterase (AChE). The lead compound, 6c1, exhibited strong BChE inhibition (IC50 = 1.74 μM), surpassing donepezil. Enzyme kinetics revealed a mixed-type mechanism, while molecular docking studies confirmed dual binding at catalytic and peripheral sites. Structure–activity relationship (SAR) analysis highlighted the influence of linker flexibility and steric/electronic effects of substituents. The observed BChE selectivity, combined with favorable in vitro profiles, identifies these hybrids as promising leads for AD drug development.